2024
DOI: 10.1039/d3ee03176d
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the temperature-responsive solvation structure and interfacial chemistry for graphite anodes

Yanbing Mo,
Gaopan Liu,
Jiawei Chen
et al.

Abstract: The variation of temperature induces a corresponding transformation of the primary solvation structure of Li+ due to the competition coordination of solvents and anions with Li+; however, the specific variations...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…This result demonstrates that the PF 6 − location undergoes a process of moving away from and approaching Li + attributing to the different high and low steric hindrance of the EMC and EC solvent, respectively. Moreover, we observed that the chemical shift of 17 O NMR in DTD moved toward the higher values from 158.74 to 158.35 ppm, resulting from the increased shielding effect on the DTD by Li + (Figure 3f). This result further demonstrates that the DTD could move closer to the Li + gradually after adding the EMC and EC solvent in a TMP-based electrolyte, weakening the Li + -TMP interaction.…”
Section: ■ Analysis Of Solvation Structurementioning
confidence: 94%
See 3 more Smart Citations
“…This result demonstrates that the PF 6 − location undergoes a process of moving away from and approaching Li + attributing to the different high and low steric hindrance of the EMC and EC solvent, respectively. Moreover, we observed that the chemical shift of 17 O NMR in DTD moved toward the higher values from 158.74 to 158.35 ppm, resulting from the increased shielding effect on the DTD by Li + (Figure 3f). This result further demonstrates that the DTD could move closer to the Li + gradually after adding the EMC and EC solvent in a TMP-based electrolyte, weakening the Li + -TMP interaction.…”
Section: ■ Analysis Of Solvation Structurementioning
confidence: 94%
“…The molecular behaviors of each electrolyte component, such as the varied Li + solvation structure, in the as-designed electrolyte can be further characterized to bolster the rationale 7 Li-(LiPF 6 ), (d) 31 P-(TMP), (e) 19 F-(LiPF 6 ), and (f) 17 of our design. Subsequently, a correlation can be established between the electrolyte properties and battery performance.…”
Section: ■ Analysis Of Solvation Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Our previous investigation suggested that LIBs retain only approximately 10% of their room-temperature capacity at −40 °C in the 1 M LiPF 6 EC/DEC/DMC electrolyte. , The poor performance at low temperature mainly arises from the sluggish desolvation at the electrode/electrolyte interphase and the slow bulk diffusion rate in the rigid crystal lattice of IEMs. As shown in Figure a, IEMs for Li ion batteries generally have a rigid structure with limited internal space that cannot accommodate solvated Li ions, and the co-intercalation of solvent molecules leads to the structural collapse of electrode materials.…”
Section: Low-temperature Batteries With Organic Electrodesmentioning
confidence: 99%